Variability in airway inflammation, symptoms, lung function and reliever use in asthma: anti-inflammatory reliever hypothesis and STIFLE study design. Issue 2 (8th June 2020) - Harrison, Tim; Pavord, Ian D.; Chalmers, James D.; Whelan, Glenn; Fagerås, Malin; Rutgersson, Annika; Belton, Laura; Siddiqui, Shahid; Gustafson, Per
Asthma is a chronic inflammatory airway disease. Increase in airway inflammation is hypothesised to contribute to worsening of asthma symptoms and deterioration in lung function, resulting in the use of reliever medication. Short-acting β2 -agonists only treat the symptoms, whereas an anti-inflammatory reliever is believed to treat both symptoms and the underlying inflammation, thereby arresting the progression to an exacerbation. As-needed budesonide/formoterol as an anti-inflammatory reliever reduces the risk of severe exacerbations. However, supporting mechanistic evidence has not yet been described, specifically the temporal dynamics of parameters including airway inflammation, over time and during asthma worsening. The STIFLE study aims to characterise daily variability in airway inflammation, symptoms, lung function and reliever use in people with asthma. This phase IV, open-label, parallel-group, multicentre, exploratory study will enrol 60–80 adult patients with asthma receiving low- or medium-dose inhaled corticosteroids/long-acting β2 -agonists (EudraCT identifier number 2018-003467-64). Participants will be randomised 1:1 to either as-needed budesonide/formoterol dry-powder inhaler or salbutamol reliever for 24 weeks, in addition to their maintenance therapy. Daily data will be captured for fractional exhaled nitric oxide, spirometry, asthma symptoms and medication use using devices connected to a smartphone via the STIFLE application. STIFLE will thereby enable not only characterisation of the variability of airway inflammation and clinical outcomes in relation to asthma worsening, but also elucidate the effect of as-needed budesonide/formoterol on airway inflammation against a background of daily maintenance therapy. Using novel, home-based tools to generate new insights into the link between inflammation and asthma attacks, the STIFLE study aims to increase understanding of the mechanisms behind the benefits of budesonide/formoterol anti-inflammatory reliever therapy https://bit.ly/33X1wJU